Learning achievement of extroverted students in algebraic operations by tutorial learning: A single subject research - Sri Adi Widodo; Desi D. Sari; Samsul Maarif; Dafid S. Setiana; Krisna S. Perbowo (International Journal of Evaluation and Research in Education (IJERE), 2022)
The purpose of this study was to improve the learning achievement of extroverted students on algebraic operations using the tutorial method. This type of research was a single subject with AB design, where A is the baseline condition, and B is an intervention condition. The research subjects were selected based on a purposive sampling technique with the help of the Keirsey Temperament Sorter (KTS) test in selecting extrovert subjects. Data collection techniques were using observation and test methods. Observation was used to collect data and record all behavior of extrovert subjects during the study. The tests in this study were the KTS and learning achievement tests. The KTS was used to determine subjects with an extroverted temperament while learning achievement tests are used to determine the ability of extrovert students to solve algebraic operation questions at the junior high school level. The results showed that the tutorial method had a positive effect on extrovert student learning achievement in algebraic operation material. This can be seen from the results of the analysis in conditions and between conditions which show that the intervention condition has a better tendency when compared to the baseline condition to the intervention. Besides that, the mean level obtained at the baseline is 50 and increases in the intervention condition with a mean level of 88.5.